Influence of the C/Sn Ratio on the Synthesis and Lithium Electrochemical Insertion of Tin-Supported Graphite Materials Used as Anodes for Li-Ion Batteries - Cédric Mercier; Raphaël Schneider; Patrick Willmann; Denis Billaud (International Journal of Electrochemistry)
Novel composites consisting of tin particles associated to graphite were prepared by chemical reduction of tin(+2) chloride by t-BuONa-activated sodium hydride in the presence of graphite. The samples obtained using various C/Sn ratios were investigated by X-ray powder diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and elemental analyses. The largest tin particles associated to graphite layers were observed for the material with a C/Sn ratio of 16. For the materials with C/Sn ratios of 42 and 24, SEM and TEM experiments demonstrated that Sn aggregates of ca. 250 nm length and composed of Sn particles with an average diameter of ca. 50 nm were homogeneously distributed at the surface of graphite. Electrodes prepared from the C/Sn=42 material exhibit a high reversible capacity of over 470 mAhg−1 up to twenty cycles with stable cyclic performances.